Redesign of the Ultimate Pit Limit Based on Re-Analysis of Lowwall Slope Stability at Pit Mahakam Barat PT Insani Baraperkasa Loa Janan Block Kutai Kartanegara Regency East Kalimantan Province - Rembang, Sonia R M; Tommy Trides; Agus Winarno; Ardhan Ismail; Windhu Nugroho (ReTII, 2025)
This research aims to perform a re-analysis of the lowwall slope stability and a redesign of the ultimate pit limit at Pit Mahakam Barat, PT Insani Baraperkasa. The analysis was conducted to evaluate the stability condition of the initial slope design and to determine an appropriate slope geometry that meets both safety and economic feasibility criteria based on the latest geotechnical conditions. The results indicate that the initial lowwall slope design has a Factor of Safety (FoS) of 1.22 and a Probability of Failure (PoF) of 13.06% under static conditions, which falls into the critical category. The redesigned slope geometry for each lithology—coal (slope angle 60°, bench height 8 m, berm width 5 m), sandstone (35°, 10 m, 7 m), and claystone–siltstone (40°, 10 m, 5 m)—produced an overall slope angle of 32°. Under dynamic conditions, the redesigned slope achieved an FoS value of 1.41 and a PoF of 1.12%, indicating a stable slope condition. Furthermore, the redesign led to an increase in both coal reserves and overburden volume. The total coal reserves increased by 14,050.16 MT, from 4,520,898.73 MT to 4,534,948.89 MT, while the overburden volume increased by 288,673.28 BCM, from 43,616,288.13 BCM to 43,904,961.41 BCM. The stripping ratio (SR) also increased slightly from 9.65 to 9.68, yet it remained below the company’s maximum economic SR limit of 11.63. Therefore, the redesigned pit is considered both technically stable and economically feasible